Cell cycle dysregulation in pituitary oncogenesis. - Muşat, M; Vax, V; Borboli, N; Gueorguiev, M; Bonner, S; Korbonits, M; Grossman, AB (2004)
The cell cycle is the process by which cells grow, replicate their genome and divide. The cell cycle control system is a cyclically-operating biochemical device constructed from a set of interacting proteins that induce and coordinate proper progression through the cycle, and includes cyclins, cyclin-dependent kinases (CDK) and their inhibitors (CDKI). There are mainly two families of CDKI, the INK family (INK4a/p16; INK4b/p15; INK4c/p18 and INK4d/p19) and the WAF/KIP family (WAF1/p21; KIP1/p27; KIP2/p57). Progression through the cell cycle is mainly dependent on fluctuations in the concentration of cyclins and CDKI achieved through the programmed degradation of these proteins by proteolysis within the ubiquitin-proteasome system. There is also a transcriptional regulation of cyclin expression, probably dependent on CDK phosphorylation. The p53 family--p53, p63 and p73--function as transcription factors that play a major role in regulating the response of mammalian cells to stressors and damage, in part through the transcriptional activation of genes involved in cell cycle control (e.g. p21), DNA repair, senescence, angiogenesis and apoptosis. Essential for the maintenance of euploidy during mitosis is human securin, identical to the product of the pituitary tumour-transforming gene (PTTG). Loss of regulation at the G1/S transition appears to be a common event among virtually all types of human tumours. Aberrations of one or more components of the pRb/p16/cyclin D1/CDK4 pathway seem to be a frequent event (80%) in pituitary tumours. The role of p27 is rather that of a haploinsufficient gene. p27-/- mice show an increased growth rate, due to increased cellularity, testicular and ovarian cell hyperplasia and infertility, and hyperplasia of the pituitary intermediate lobe with nearly 100% mortality caused by such a benign pituitary tumour. Although the p27 gene was not found to be mutated in human pituitary tumours and its mRNA expression was similar in tumour samples in comparison with normal pituitaries, the load of p27 protein expression in corticotroph adenomas and pituitary carcinomas was shown to be much lower than those in normal pituitary tissue or other types of pituitary adenoma, suggesting that post-translational processing of p27 accelerates its removal from the nucleus. In respect to p27 degradation and its cellular compartmentalization, several pathways have been explored. Malignant tumours are associated with increased nuclear immunostaining for Jun-activation binding protein-1 (Jab1) which is responsible for phosphorylated p27 export from the nucleus. Corticotrophinomas are characterized by massively increased phosphorylation of p27 on Thr187, but are not associated with changes in Jab1. Macrophage inhibitory factor (MIF), which binds and inactivates Jab1, was noted to be over-expressed in tumours with abundant Jab1, suggesting that it may be part of a compensatory mechanism to moderate Jab1 activity. Proteasomal degradation of p27 requires its ubiquitylation by the SCF ubiquitin ligase, with specific addressing by the F-box protein Skp2 and its co-factor Cks1. Pituitary tumours with high p27 protein expression showed significantly less Skp2 expression than samples with low p27 immunostaining, suggesting that increased Skp2 could play at least a part in this process. No difference was observed in Cks1 mRNA levels between normal pituitaries and pituitary adenomas. The present data suggest that inhibition of growth and tumour development is sensitive not only to the absolute levels of p27 protein, but also to its cellular compartmentalization. Very recent findings from our group have established up-regulation of the serine-threonine kinase Akt in pituitary tumours compared to normal pituitary, which may cause phosphorylation of p27 on Thr157 and cytoplasmic retention of p27. PTTG protein is highly expressed in various human tumours, including pituitary tumours. While its mRNA levels are low in normal pituitary, increases in PTTG transcripts from more than 50% to more than 10-fold were recorded in the majority of a series of pituitary adenomas. Control of the cell cycle is a vital part of the cell's replication machinery. Disruption of this process is commonly seen in pituitary tumours and we are now beginning to identify regulatory elements which are likely to play a major role in pituitary oncogenesis.